Analysis of recurrent urinary tract infection (UTI) in University Hospital – approach of antibiotic resistance in clinical isolates - Alves, Danilo Antonini (2022)
The fifty-two bacteria were isolated from urinary tract infections in University Hospital in Sumaré, São Paulo State, Brazil.  These isolates were analyzed about their antibiotic resistance and their bacterial characteristics. Around percentage from these isolates were identified as belonging to Escherichia coli strains, followed by Klebsiella pneumoniae and Pseudomonas aeruginosa. The multiresistance profile (resistance profile major than four 4 antibiotic classes) were viewed in thirteen (13) strains of Escherichia coli, sixteen (16) strains in Klebsiella pneumoniae (being two (2) carbapenem resistant suggesting an existence of KPC strain). The results had demonstrated an indiscriminate antibiotic use concentrated in the increase of quinolones resistance (principally in ciprofloxacin use), and also the rise of KPC super bacteria.